Versatile biocatalysis of fungal cytochrome P450 monooxygenases. Issue 1 (December 2016) - Durairaj, Pradeepraj; Hur, Jae-Seoun; Yun, Hyungdon
Abstract Cytochrome P450 (CYP) monooxygenases, the nature's most versatile biological catalysts have unique ability to catalyse regio-, chemo-, and stereospecific oxidation of a wide range of substrates under mild reaction conditions, thereby addressing a significant challenge in chemocatalysis. Though CYP enzymes are ubiquitous in all biological kingdoms, the divergence of CYPs in fungal kingdom is manifold. The CYP enzymes play pivotal roles in various fungal metabolisms starting from housekeeping biochemical reactions, detoxification of chemicals, and adaptation to hostile surroundings. Considering the versatile catalytic potentials, fungal CYPs has gained wide range of attraction among researchers and various remarkable strategies have been accomplished to enhance their biocatalytic properties. Numerous fungal CYPs with multispecialty features have been identified and the number of characterized fungal CYPs is constantly increasing. Literature reveals ample reviews on mammalian, plant and bacterial CYPs, however, modest reports on fungal CYPs urges a comprehensive review highlighting their novel catalytic potentials and functional significances. In this review, we focus on the diversification and functional diversity of fungal CYPs and recapitulate their unique and versatile biocatalytic properties. As such, this review emphasizes the crucial issues of fungal CYP systems, and the factors influencing efficient biocatalysis.